The WTO and direct taxation - Daly, Michael (ECLAC SantiagoCL, 2005)
Provides an overview of the extent to which present WTO rules apply to taxation, particularly direct taxation. Contains a summary of disputes concerning income tax measures that have arisen at the WTO since its establishment, with special attention to the protracted dispute between the EC and the US over the latter's FSC/ ETI schemes. Focuses on some issues regarding direct taxation that have been identified in recent trade policy reviews; the tax policies and measures involved do not necessarily contravene WTO rules. Provides a comparision of the rationale and principles underlying WTO rules and those underlying international taxation. Reviews some recent empirical evidence regarding the incidence of direct taxes.